Where do new firms locate? The effects of agglomeration on the formation and scale of operations of new firms in Punjab - Maryiam Haroon; Azam Chaudhry (Kiel Institute for the World Economy (IfW), 2014)
The formation of new firms is an important determinant of economic development and the industrial organization literature highlights agglomeration as one of the main factors affecting the formation and scale of operations of new firms. This paper is one of the first to use developing country data to estimate the impact of localization (the benefits accruing to firms that choose to locate in a specific region within a specific industry) and urbanization (the benefits accruing to firms located close to each other regardless of the type of industry to which they belong) on new firms' formation and scale of operations. Our findings reveal that agglomeration measured through density of employment has a significant impact on the formation of new firms and on their scale of operations in Punjab.
Keywords: L1; L2; 330; agglomeration; firms; localization; urbanization